Numerical Investigations On Sprue Configuration For Multi-Cavity Mould - Badrul Hisham, Alya Nabilah (Universiti Sains Malaysia, 2022)
Polypropylene is a thermoplastic addition polymer which is made up of several propylene monomers. PP is a popular material used commercially as it is a versatile material. Manufacturing of PP products through injection moulding and extrusion is common. Injection moulding is a manufacturing technique that enables large-scale production of items which includes injecting molten materials into a mould. The overall goal of the study is to better understand how PP flows during injection moulding. The first goal is to design a sprue configuration for multi-cavity mould. The second objective is to conduct numerical investigations on the configuration to find the pressure in the runners, and fluid velocity during injection. The final objective is to compare the flowability between commercial grade PP and medical grade PP. The investigation is done by conducting a numerical simulation, which is carried out using Ansys Fluent 2020 R1, while the sprues are meshed in Ansys Mechanical 2021 and modelled in SolidWorks 2020. The simulation results show that higher injection pressure (49 MPa) results in higher runner pressure (26466.66 KPa) as well as the fluid velocity (256.06 m/s) which gives lower fill time (0.91615 s) as opposed to lower injection pressure (45 MPa). On the other hand, higher injection temperature (220°C) results in runner pressure (27973.42 KPa) but lower fluid velocity (233.34 m/s) which gives lower fill time (0.90745 s) as opposed to lower injection temperature (180°C). This phenomenon may occur due to shear thinning which influence the viscosity of a non-Newtonian fluid where the viscosity decreases under shear strain Other than that, the medical grade PP LB6331 generally has a higher flowability than the commercial grade PP TP6331 due to exhibiting higher runner pressure (26888.08 KPa), higher fluid velocity (257.02 m/s), and lower fill time (0.93265 s).